Genotyping circulating tumor DNA of pediatric Hodgkin lymphoma - Desch, Ann Kathrin; Hartung, Kristin; Botzen, Ante; Brobeil, Alexander; Rummel, Mathias; Kurch, Lars; Georgi, Thomas; Jox, Theresa; Bielack, Stefan; Burdach, Stefan; Classen, Carl Friedrich; Claviez, Alexander; et al. (Leukemia, 2019)
We used hybrid capture-targeted next-generation sequencing of circulating cell-free DNA (ccfDNA) of pediatric Hodgkin lymphoma (PHL) patients to determine pathogenic mechanisms and assess the clinical utility of this method. Hodgkin-Reed/Sternberg (HRS) cell-derived single nucleotide variants, insertions/deletions, translocations and VH-DH-JH rearrangements were detected in pretherapy ccfDNA of 72 of 96 patients. Number of variants per patient ranged from 1 to 21 with allele frequencies from 0.6 to 42%. Nine translocation breakpoints were detected. Genes involved in JAK/STAT, NFkB and PI3K signaling and antigen presentation were most frequently affected. SOCS1 variants, mainly deletions, were found in most circulating tumor (ct) DNAs, and seven of the nine translocation breakpoints involved SOCS1. Analysis of VH-DH-JH rearrangements revealed an origin of PHL HRS cells from partially selected germinal center B cells. Amounts of pretherapy ctDNA were correlated with metabolic tumor volumes. Furthermore, in all ccfDNA samples of 43 patients with early response assessment quantitative qPET < 3, indicative of a favorable clinical course, ctDNA was not detectable. In contrast, in five of six patients with qPET > 3, indicative of an unfavorable clinical course, ctDNA remained detectable. ccfDNA analysis of PHL is thus a suitable approach to determine pathogenic mechanisms and monitor therapy response.
CRIS-Team Scopus Importer:2019-08-27